The effect of preoperative vaginal preparation with povidone-iodine on post-caesarean section infection - Ayodeji Emmanuel Agbana; TOLA YINKA BAKARE; Julius Kolajo Dare; Muideen Gbenga Adesola; Hafeez Ayotunde salawu; Adebunmi Olarinoye; Adegboyega Adisa Fawole (Babcock University Medical Journal)
Objective: To evaluate the effect of preoperative vaginal antiseptic cleansing with Povidone-iodine on the occurrence of post-caesarean section infectious morbidity.